Strategi Humas Polisi Resort Kota Samarinda dalam Menangani Berita Hoax di Samarinda - Rozalia Fitriany Oedi; Endang Erawan; Kadek Dristiana Dwivayani (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
In the run-up to the presidential election in 2019, hoax news is increasingly spreading as a black campaign, namely vilifying each other between opposing political camps. This study aims to determine the communication strategy of the Samarinda Police Public Relations in handling hoax news for the 2019 presidential election in Samarinda City. The focus of this research is 7-‐‑Cs PR Communications initiated by Cutlip, Center & Broom. 7C itself consists of, Credibility, Context, Content, Clarity, Continuity and Consistency, Channel, and Capability of the audience. Data collection techniques in this study used three ways, namely observation, interviews and documentation. The results showed that the Public Relations of the Samarinda Police has a very important position to handle hoaxes ahead of the 2019 Presidential Election. Public Relations has made observations, clarifications, confirmations, and validations as a quick response to hoaxes. Public Relations has provided communication services from institutions to the community through socialization or counseling as well as regularly on social media and all are supported by technological advances so as to make performance in the process of delivering information faster and more accurate.